Expectativas de jovens que vivem em assentamento: um estudo sobre a tríade trabalho-educação-família - OLIVEIRA, Rosa de Souza (Universidade Federal do Pará, 2011)
The present study tried to understand the young expectations that live in the establishment Luiz Lopes Sobrinho, located in the Municipal District of San Francisco of Pará. It is a research characterized as quantitative and qualitative, once the data had statistical and interpretative treatment with base in the content analysis. The Stratified Random Probability Method was used for the selection of the sample. The instruments of collection of data were the following ones: the direct observation and the interview through form and of itinerary. The corpus of the research was constituted in the speech of thirty young of the gender masculine or feminine, in the age group from 15 to 24 years and that they belong an origin family or of reproduction. The conclusive approaches revealed that the youth production of that establishment, in general, nurtures expectations of exercising activities different from the farming, with the purpose of improving their life condition; it wants to transmit values and social rules, aiming at to give continuity to the you know acquired in the origin family; it hopes to get a work/employment/professional formation, looking for a sense the own existence, as well as wants to constitute family, to have a companion and children with the purpose of reproducing the model of effective family. Those hopes, in its group, moderate for the sphere of politics that make possible rural development.